Meetings of the chapter (can. 506 § 1) - ADAMCZYK, JERZY (Prawo Kanoniczne, 2019)
The aim of the article is to present the legal aspects of the chapter meetings in the light of applicable law. The first part elaborates on the issue of convening chapter meetings. The second part depicts the problem of the participants of the chapter sessions, the third part deals with the course and subject of the canonical debates. Finally, the fourth part is dedicated to the issue of adopting resolutions by the canons. The article ends with conclusions and references.